(untitled) (Conference Zone, 2022)
One of the most important goals of the modern higher education system is to prepare competitive specialists who have a high level of professional training and are well-rounded as individuals, who are able to work tirelessly on deepening and expanding their knowledge and skills throughout their lives. In the complex complex of psychological and pedagogical factors determining the effectiveness of students’ educational activities, the following are distinguished: psychological content and structure of educational motivation, individual psychological characteristics, characteristics of self-organization of students. Since the success of educational activity is an integral part of personality formation, this problem has not lost its relevance until now.